The Coherence of Surah Adz-Dzariyat in Perspective of Semitic Rhetoric - Asnawi, Aqdi Rofiq; Suharto, Ahmad; Shahir, Muhammad Badrun; Anggara, Deki Ridho Adi; Hannah, Hannah (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
The order of the verses and their coherence has been debated among orientalists in qur’anic structure studies. This article aims to reveal the coherence of the surah Adz-Dzariyat questioned by Richard Bell regarding the correlation between the verses in the surah. The method of analyzing this surah is Semitic Rhetorical Analysis (SRA), utilizing the verses’ symmetry explanations from Muslim scholars’ interpretations. This library research adopts descriptive and content analysis methods for analyzing data. As a result of the study, Surah adz-Dzariyat consists of two passages and seven parts in mirror construction based on Semitic Rhetoric principles. The relationship between the verses shows their coherence and excellent verse order without jumpy arrangements. Several groups of verses that at first appeared to be irregular became orderly and had a specific connection that could be understood through Semitic Rhetoric principles. This analysis strengthens the miracles of the Qur’an and refutes various opinions that doubt how good the order of the verses of the Qur’an is.